2023
DOI: 10.1590/1519-6984.252656
|View full text |Cite
|
Sign up to set email alerts
|

The molecular investigations on the subgenus Artemisia Less. of the genus Artemisia L. (Asteraceae) in Turkey

Abstract: The genus Artemisia L. of the family Asteraceae is systematically very complex. The aim of this study was to evaluate taxonomic positions of taxa of the subgenus Artemisia belonging to the genus Artemisia in Turkey using some molecular techniques. In this molecular study, 44 individuals belong to 14 species of the subgenus Artemisia were examined. Analyses were performed on the combined dataset using maximum parsimony, maximum likelihood and Bayesian inference and Molecular parameters obtained from co-evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Molecular characterization studies carried out in recent years give important ideas about the systematics of species [ 9 , 10 , 11 , 12 , 13 ]. Genetic characterization studies among Salvia species have also revealed a large genetic variation among species.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular characterization studies carried out in recent years give important ideas about the systematics of species [ 9 , 10 , 11 , 12 , 13 ]. Genetic characterization studies among Salvia species have also revealed a large genetic variation among species.…”
Section: Introductionmentioning
confidence: 99%
“…However, the periderm layer was quite thick in our study. In the taxonomic evaluation of plants, morphological, anatomical, moleculer studies of the species are of great importance [10][11][12][13][14]. The stem and root anatomy of the R. caespitosa species was determined through this study.…”
Section: Discussionmentioning
confidence: 99%
“…It contains almost 500 species of both herbs and shrubs and is a diverse genus of the Anthemideae tribe (Hussain, 2020). Artemisia genus is represented by 27 taxa, including 21 species, 3 subspecies and 3 varieties in Turkey (Sancar et. al., 2021).…”
Section: Introductionmentioning
confidence: 99%